Autologous platelet-rich plasma in the treatment of refractory corneal ulcers: A case report - Miguel Rechichi, MD PhD; Marco Ferrise, MD Febo; Francesco Romano, MD; Luca Gallelli, MD; Vincenzo Toschi; Andrea Dominijanni; Alessandro Meduri, MD (American Journal of Ophthalmology Case Reports, 2020)
Purpose: To evaluate the efficacy of a low-cost preparation of platelet-rich plasma (PRP) eye drops in the treatment of persistent non-infectious corneal ulcer. Observations: A 67-year-old female presented to our clinic with a wide corneal ulcer and severe paracentral corneal thinning refractory to medical therapy with antibiotics, lubricant and contact lens bandage. The patient received a novel preparation of PRP solution. After 15 days of therapy, we observed complete resolution of the corneal ulcer with regrowth of the epithelium and a reduction in corneal opacity. Conclusion and importance: Although the low-cost PRP preparation gives a lower platelet concentration than standard procedures, our work shows this preparation to be effective in the treatment of refractory non-infectious corneal ulcer.